Connectivity is a key resource pending resolution for digital transformation in Perú - Pimentel Serrano, Wilfredo Elias; Valladolid Marcos, Fiorella Sthefany; Alzamora De Los Godos Urcia, Luis Alex; Calderón Saldaña, Jully Pahola (LACCEI, 2023)
Abstract— In recent decades, digital technology has radically transformed the functioning of economies and has established itself as a fundamental driver of economic growth globally. The Kazt 2022 Report highlights the significant impact that digital development has on the Gross Domestic Product (GDP) through variables related to connectivity, transformation and digital development of countries. According to this report, a 10% increase in broadband development is expected to have an effect of more than 1.5% on GDP growth in the countries of the Latin American region. This document presents a study that analyzes the influence of connectivity and digital development variables in Peru. For this, four variables common to 10 other comparison countries have been selected as a reference. Regression calculations have been carried out to determine the degree of explanation and significance of these variables in the Peruvian GDP. The results obtained indicate that the connectivity variables studied, in the period from 2017 to 2023, do not have a relevant impact on Peru’s GDP. After simplifying the model to two variables and extending the analysis period to 2013-2023, a regression was achieved with an acceptable coefficient of determination and a significant analysis of variance. In this context, projections and predictions have been made for Peru’s GDP, identifying that under current conditions, these variables would only contribute to an average increase of 7%, three points below the expected value according to the Kast Report. When carrying out the projection and prediction calculations with the simplified model, and when considering digital development values of connectivity variables from other countries, such as Uruguay for example, it has been observed that the Peruvian GDP for the year 2023 could have reached a higher level. by 23%. The low levels of growth in the connectivity variables under analysis in Peru limit its possibilities to accelerate digital transformation, close digital gaps, achieve the Sustainable Development Goals by 2030 and establish an advanced Information Society